Performance Evaluation of Hydrocyclone Filter for Drip Irrigation- PSD Approach - Rao, M Damodhara; Thomas, K John (Journal of Agricultural Engineering, 2005)
In this study a commercially available hydrocyclone filter of size 20 cm was selected to evaluate its performance in separating the particulate matter by Particle Size Distribution (PSD) approach. The filter was tested with four different concentrations of soil suspension, 300, 600, 900, 1200 mg/l for 10 hrs duration each. The under flow particulate matter was collected at the end of each experiment and it was analysed by standard sieve technique. It was found that the amount of underflow particulate matter having particle size more than 300 microns is almost same for all inflow concentrations. The amount of finer pmticles which are less than or equal to 300 microns, decreased with the increase of inflow concentration. The overall results show that the filter may give finer separation of particles of lower concentrations and the separation of coarser particles are same irrespective of the concentration of soil suspension.